Analysis The Effect of Water Quality and Service Quality on Consumer Loyalty - Riska Iva Riana (PT. SAFARI AMALIA, 2025)
Sustainability of water supply services hold contributes to human well-being with individual preferences. So, there is need to assess for the public from various levels of water services in an effort to ensure water provision with the aim of achieving customer satisfaction in its use so that it can build their own loyalty. So therefore, this study was conducted to determine how water quality and service effect consumer loyalty using the Structural Equation Modeling (SEM) by looking for variables that influence quality and success in achieving user loyalty by forming a diagram of the relationship between variables and indicators, confirmatory analysis factors for exogenous and endogenous variables in the initial model, data normality tests and outlier evaluations. The model fit test in this study uses several criteria, including Chi Square, GFI, TLI, CLI, AGFI and RMSEA. Based on the results of this study, it shows that (1) the variable (CS) Consumer Satisfaction value of 0.768, meaning that the variable (CS) Consumer Satisfaction can be explained by (WQ) Water Quality (SQ) Service Quality with a percentage value of 76.8% while 24.2% can be explained by other variables not examined in this study. (2) not all antecendent variables have a significant influence on the consequent variables. Also, not all hypotheses are accepted. All antecedent variables cannot explain the consequent variables because the R2 value is less than 0.5.